Short Communication: DNA barcodes and phylogenetic of striped snakehead and ocellated snakehead fish from South Sumatra, Indonesia - MOCHAMAD SYAIFUDIN; MARINI WIJAYANTI; SEFTI HEZA DWINANTI; MUSLIM MUSLIM; MUHAMMAD MAHENDRA; SHELY MARLIANA (Society for Indonesian Biodiversity, 2020)
Abstract. Syaifudin M, Wijayanti M, Dwinanti SH, Muslim, Mahendra M, Marliana S. 2020. DNA barcodes and phylogenetic of striped snakehead and ocellated snakehead fish from South Sumatra, Indonesia. Biodiversitas 21: 1227-1235. This research aimed to identify the sequences of cytochrome c oxidase subunit I gene mitochondrial DNA (COI mtDNA), to construct a phylogenetic tree of striped snakehead (Channa striata) and ocellated snakehead (Channa pleuropthalma), and to measure water quality of Kelekar River, Indralaya, Ogan Ilir District and Danau Burung Besar River, Penukal Abab Lematang Ilir (PALI) District in South Sumatra, Indonesia. The research procedures consisted of DNA isolation, amplification by PCR (Polymerase Chain Reaction) and sequencing of fragment COI mtDNA. The length of nucleotide was 604 bp for striped snakehead and 587-604 bp for ocellated snakehead. Optimum annealing temperature was 500C for 15 seconds with 30 cycles. The result of BLAST analysis showed that striped snakehead from Kelekar and Danau Burung Besar River had 100% identity to striped snakehead from Java-Bali and furthest (97%) with striped snakehead from India. Ocellated snakehead had 100% similarity with the same species from Musi Banyuasin and Banjarmasin; and furthest (83%) with Channa limbata from Myanmar. Water quality in Kelekar River were temperature 31-31.60C, pH 4.76-4.96, dissolved oxygen 2.7-3.0 mg/L, ammonia <0.009 mg/L, total alkalinity 20 mg/L, and turbidity 62.5-63 cm. Meanwhile in Danau Burung Besar River showed temperature (29.3-30.70C), pH (3.6-6.7), dissolved oxygen (1.31-3.76 mg/L), ammonia (0.17-0.20 mg/L), and turbidity (50-90 cm).